2018
DOI: 10.24200/sci.2018.50750.1850
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of traditional and online group-buying channels considering website promotion effort

Abstract: The development of modern technology and e-commerce has given rise to the emergence of many new selling channels, among which group buying has managed to attract numerous new customers rapidly because of such features as good discounts and great convenience. Although a good discount scheme creates sales growth for sellers, it also causes loss in their pro t margins. Meanwhile, the business model of group-buying websites is not thoroughly explored in literature. Based on a Stackelberg game framework, this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…For example, Ni [12] considered both positive and negative network effects and proposed three possible sales strategies for group buying, individual buying, and hybrid buying, as well as their optimal decision on price. Wu et al [13] studied the method for restaurants to set group buying prices and the optimal promotion strategy for the platform, given the promotion level of group buying websites. He et al [14] explored fairness-focused behavior in the group buying supply chain and found that the retailer's fairness-focused behavior does not always harm the supplier's profits.…”
Section: Online Group Buying Pricing Strategiesmentioning
confidence: 99%
“…For example, Ni [12] considered both positive and negative network effects and proposed three possible sales strategies for group buying, individual buying, and hybrid buying, as well as their optimal decision on price. Wu et al [13] studied the method for restaurants to set group buying prices and the optimal promotion strategy for the platform, given the promotion level of group buying websites. He et al [14] explored fairness-focused behavior in the group buying supply chain and found that the retailer's fairness-focused behavior does not always harm the supplier's profits.…”
Section: Online Group Buying Pricing Strategiesmentioning
confidence: 99%
“…For example, Jiang et al [15] explore the impact of enterprises' honesty strategy on building a healthy SGB environment under government supervision; He et al [11] discuss the optimal SGB strategy for different enterprises with fairness concerns in the supply chain. Besides, because social cost inhibits consumers' recommending motivation on social networks [4], it negatively impacts the ECPS marketing channel [37]. Therefore, based on the previous SGB models, we focus on the social cost and design a forwarding-bargaining model with multiple iterations to study the ECPS channel.…”
Section: Ecps Marketing Channelmentioning
confidence: 99%
“…they represent an analytical model with finite capacity to optimize GB price and maximum deal size limit. Wu, Li and Li [25] consider a group-buying website and a seller to find an equilibrium between them. The results show that the scale of the seller and the website influence the optimal decisions in the whole system.…”
Section: Literature Reviewmentioning
confidence: 99%